Contemporary Da'wah Strategies to Educate the Religious Life of Minority Muslims - Nazrial Amin (STAI Serdang Lubuk Pakam, 2022)
Contemporary preaching is not something easy for preachers to do, especially in the midst of a minority community an understanding of religion is still shallow. The preachers need intelligence so that there is no horizontal conflict. This study aims to discover how contemporary da'wah strategies foster religious life and the supporting factors and facilitating factors of contemporary da'wah strategies in promoting community religious life in Lau Gumba Village, Karo Regency. This study uses qualitative research methods using a case study approach, collecting data using observation techniques, interviews and documentation studies. The results of the research show that the strategies used are: (1) Preaching through media and equipment, such as projectors and PowerPoint slides, with the aim of making it easier for people to understand the material; (2) approaching religious leaders, village heads and traditional leaders to attract community sympathizers, (3) applying the notion of religious moderation which upholds the values ​​of religious tolerance. The supporting factor is the high motivation of the community to maintain religious harmony through a good understanding of religion. Meanwhile, the difficulty in the contemporary da'wah strategy is understanding the people's religion, which is still categorized as low.